WORD STRESS IN ENGLISH AND UZBEK - Khalilova Bakhora; Yakubov Fakhriddin (TADQIQOTLAR, 2025)
Annotation:This  article  examines  the  concept  of  word  stress  in  the  English language and its importance in correct pronunciation and effective communication. Word stress plays a crucial role in distinguishing meaning, improving intelligibility, and developing listening and speaking skills. The article discusses the definition of word  stress,  its  main  types,  and  common  stress  patterns  in  English  words. Special attention is given to the difficulties faced by Uzbek learners of English and the typical mistakes  they  make  in  stress  placement.  The  study  highlights  the  significance  of teaching word stress systematically and suggests practical approaches for improving learners’ pronunciation competence.